Diseño de un programa de rehabilitación de ligamento cruzado anterior en pacientes atendidos en el centro de acondicionamiento físico Fitness Park en los meses de febrero-marzo de 2008 (2008)
The anterior cruciate ligament is a ligament that is in the knee, which runs between the femur and tibia in oblique sense. Its function is to curb the anterior displacement of the tibia, limiting the rotation and tibial angle in length. It is now one of the most important and feared injury in sports, because this ligament is the most exposed to damage and injuries caused by their anatomy. This injury is due to a sudden change in the direction of the knee at slowing down sharply, for example to fall ill and support the limb after a jump, or to stop abruptly after running, is the female which showed a more impact injury to the ACL given its anatomical features: greater laxity articulate, pelvis wider than external conditions rotation of the tibia, the venue hosts the ACL in his knee (notch) is proportionately lower than in males.